A Comparative Analysis of the Strategy and Structure of United States and Australian Corporations - Capon, Noel; Christodoulou, Chris; Farley, John U.; Hulbert, James M. (Journal of International Business Studies, 1987)
An analysis of the environments of leading manufacturing firms operating in the United States and in Australia produced a series of hypothesized differences in the strategies, organization structures, and market environments of firms in the two countries. Parallel hypotheses about differences between domestic Australian firms and subsidiaries of foreign multinationals operating in Australia were also developed.